ANALYSIS OF SOCIAL MEDIA MARKETING STRATEGY (GOFOOD) IN INCREASING CONSUMERS AT WARUNG SOTO PAK KOYA KRAKSAAN SHARIA ECONOMIC PERSPECTIVE - Ismatul Maula (IJED: International Journal of Economy Development Research, 2023)
Social media marketing strategies have become a crucial element in the development of culinary businesses, playing a key role in acquiring and retaining customers. By leveraging the GoFood platform, Warung Soto Pak Koya has designed and implemented a series of strategies aimed at increasing the number of consumers. This research focuses on Warung Soto Pak Koya, a soto stall located in Kraksaan, and investigates the effectiveness of social media marketing strategies, especially through the GoFood platform, in increasing the number of consumers. The objectives of this research are to understand the social media marketing strategies (GoFood) in increasing consumers at Warung Soto Pak Koya Kraksaan and to determine the impact of GoFood marketing strategies on Warung Soto Pak Koya in enhancing consumer numbers. The research method applied by the author is a qualitative research method through a case study at Warung Soto Pak Koya. Data collection techniques include observation, testing, interviews, and documentation. The results obtained from this research are as follows: the social media marketing strategies through GoFood at Warung Soto Pak Koya Kraksaan include uploading a complete menu, optimizing taste quality, offering special GoFood promotions, and analyzing performance. The impact of social media marketing strategies through GoFood in increasing consumers is positive, although the increase in consumers is not as significant as before using the GoFood platform.